Panel evidence on within-occupation change in job tasks and individual wages - Gerrit Müller (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
Drawing on newly available panel data, this paper presents an empirical analysis of the wage effects of changing job tasks, assessed for individuals at their workplace. I am therefore able to exploit within-occupation within-individual variation, over time, to study wage returns to cognitive, interpersonal, physical and routine task intensity. The findings of Autor and Handel's (2013) pioneering work on the significance of such within-occupation ("intensive margin") task variation are reassessed. Unobserved worker attributes and ongoing self-selection into occupations can be accounted for in a much more comprehensive way than possible with purely cross-sectional data, as in the original work. – – Auf Grundlage neu verfügbarer Paneldaten präsentiert dieses Papier eine empirische Analyse der Lohneffekte sich verändernder Tätigkeiten am individuellen Arbeitsplatz. Unter Ausnutzung der Datenvariation innerhalb von Berufen und Individuen, über die Zeit, werden Lohnrenditen für die Ausübung von kognitiven, interpersonalen, physischen und Routine-Tätigkeiten geschätzt. Die Erkenntnisse der einflussreichen Studie von Autor und Handel (2013) über die Bedeutung des Tätigkeitswandels innerhalb von Berufen ("intensive Margin") werden erneut untersucht. Insbesondere kann individueller unbeobachteter Heterogenität und Selbstselektion in Berufe besser Rechnung getragen werden, als dies in der ursprünglichen Querschnittsstudie möglich war.
Keywords: J24; J31; 330; Job tasks; occupations; routine-biased technical change; wages; workplaces